2022
DOI: 10.2478/pjmpe-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bismuth Oxide Nanoparticles, Cisplatin and Baicalein-rich Fraction on ROS Generation in Proton Beam irradiated Human Colon Carcinoma Cells

Abstract: Introduction: Proton beam radiotherapy is an advanced cancer treatment technique, which would reduce the effects of radiation on the surrounding healthy cells. The usage of radiosensitizers in this technique might further elevate the radiation dose towards the cancer cells. Material and methods: The present study investigated the production of intracellular reactive oxygen species (ROS) due to the presence of individual radiosensitizers, such as bismuth oxide nanoparticles (Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The DEF values of BRF were calculated from the theoretical Z eff of the BRF, which approximates a carbon element. 54 This divergence between SER values and DEF values of BRF suggested that, biologically, natural compounds could not fully mimic the actions of the carbon element. The different effects between BRF and carbon could be related to research on carbon fiber implants which found that carbon could neither increase nor decrease the radiation dose in radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DEF values of BRF were calculated from the theoretical Z eff of the BRF, which approximates a carbon element. 54 This divergence between SER values and DEF values of BRF suggested that, biologically, natural compounds could not fully mimic the actions of the carbon element. The different effects between BRF and carbon could be related to research on carbon fiber implants which found that carbon could neither increase nor decrease the radiation dose in radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…The Z eff of BRF, Cis, and BiONPs had been calculated in our previous research, which are 6, 62, and 78, respectively. 40 , 54 These Z eff values are approximate to carbon, samarium, and platinum metals, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than this, bismuth salts were found to be effective in the treatment of syphilis, hypertension, dyspepsia, diarrhea, H-pylori infection, etc. [45][46][47][48][49][50]. Among the various compounds of bismuth, colloidal bismuth subcitrate (CBS), bismuth subnitrate (BS) [51,52], bismuth subsalicylate (BSS), and ranitidine bismuth citrate (RBC) are explored in the literature for their effectiveness and mode of action as well as modifications [53][54][55][56].…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Bismuth salts exhibit antibacterial action against various gastrointestinal tract pathogens including E-coli, Salmonella, Vibrio cholera, etc. [46]. The mechanism of bactericidal action of bismuth is still unclear, but several proposed mechanisms are summarized in Figure 3B [41].…”
Section: Antibacterial Actionmentioning
confidence: 99%